Effect of Plant Extracts and Essential Oil Blend as Alternatives to Antibiotic Growth Promoters on Growth Performance, Nutrient Utilization and Carcass Characteristics of Broiler Chicken - Devi, Pebam Chandrima; Samanta, A. K. (Indian Journal of Animal Nutrition, 2018)
A study was conducted to assess the effect of dietary supplementation of plant extracts and essential oils on performance of broiler birds, nutrient utilization and carcass traits of broiler birds. Â Two hundred one day old broiler chicks were randomly distributed into five treatment groups with five replicates containing eight birds in each replicates. Dietary groups consisted of : 1) basal diet Â as per BIS standard ,2007 without any supplementation (control); 2) basal diet with BMD (Bacitracin methylene disalicylate) @.5g/kg of feed (AB); 3) basal diet supplemented with methanolic extracts of Mikania micrantha and Garcinia lanceaefolia @ 2.79 g/kg and 1.39 g/kg of feed respectively. 4) basal diet supplemented with Essential oil (Cinnamon and ajawain @ 3 g/kg and 4 g/kg of feed respectively; and 5) basal diet with plant extracts and essential oil combination at same dose rate. Metabolic trial was conducted at the end of feeding trial . One chicken from each replicate was slaughtered for measurement of carcass traits. Broiler birds fed AB, PE, EO and PEO increased (P<0.01) ADG, body weight, FCR and EPEI during the overall the period (d 1-42). PE groups showed significantly lower feed intake (P<0.01) compared to other treatment groups. Apparent digestibility of dry matter and other nutrients was not affected due to supplementation of AB, PE, EO and PEO. Carcass characteristics showed no significant difference (p>0.05) among the treatment groups. Organoleptic test revealed that overall acceptability of meat was significantly higher (P=0.008) in PE, EO & PEO groups compared with control & AB groups. It can be concluded that supplementation of methanolic extracts of Mikania micrantha and Garcinia lanceaefolia and Essential oil blend (Cinnamon and Ajwain oil) can be used as natural alternative to antibiotic growth promoters to improve the performance of broiler birds.